Associations between human milk EV-miRNAs and oligosaccharide concentrations in human milk - Holzhausen, Elizabeth A.; Patterson, William B.; Wong, Benjamin H.; Kim, Sewan; Kupsco, Allison; Howe, Caitlin G.; Bode, Lars; Goran, Michael I.; Alderete, Tanya L. (Frontiers in Immunology, 2024)
IntroductionHuman milk contains human milk oligosaccharides (HMOs) and microRNAs (miRNAs), which are key bioactive components. HMOs are indigestible carbohydrates that impact infant growth and development. miRNAs are small, non-coding RNAs that regulate post-transcriptional gene expression. miRNAs are abundant in human milk and can be contained in extracellular vesicles (EVs). There is evidence that miRNAs are synthesized in the mammary epithelium and may influence mammary gland development and milk synthesis. However, the relationships between miRNAs and HMOs have yet to be fully characterized.MethodsThis study examined the associations between 210 human milk EV-miRNAs and 19 HMOs in a cohort of 98 Latina mothers. HMO measures included summary measures and concentrations of 19 HMOs. Relationships between EV-miRNAs and HMOs were examined using principal components analysis and associations between individual EV-miRNAs and HMOs were assessed.ResultsOverall patterns of EV-miRNA levels, summarized using principal components, were associated with HMO summary measures and concentrations. Levels of individual EV-miRNAs were associated with HMO summary measures and individual concentrations of 2’FL, 3FL, 3’SL, 6’SL, FLNH, LNFP I, and LNH.DiscussionResults from this study suggest that human milk EV-miRNAs are associated with the concentration of HMOs, which may have important effects on infant growth and development.